Mental models and creative thinking skills in students’ physics learning - Batlolona, John Rafafy; Diantoro, Markus (Creativity Studies, 2023)
The study of mental models and creative thinking skills in students’ physics learning with the problem-based learning model has been scarce. This study aimed to analyze the relationship between mental models and creative thinking skills in high school students. Many previous research findings explain a relationship between mental models and creative thinking skills among students at the university level and workers. This mixed-methods study was conducted on high school students in Malang, East Java, Indonesia, aged between 14 and 15 years. The instrument used is in the form of mental models and creative thinking skills test questions. This finding explains no relationship between mental models and creative thinking skills because learning has not fully empowered mental models and creative thinking skills. On the other hand, learning at the previous level, students’ knowledge is still fragmented, so that is incomplete. Therefore, at the high school level, they need help to improve their mental models and creative thinking skills. This finding implies that teachers in developing learning materials, tools, and instruments must pay attention to the level of student knowledge so that learning can be more optimal.